Shelling characteristics of green pea pods - Singh, Daya S (Journal of Agricultural Engineering, 2006)
Investigations were carried out to know the effect of moisture content and pod size on shelling efficiency of the power operated green pea pod shelling machine developed at Jabalpur centre of PHTS. Moisture levels of 68.5 to 75.7% (wb) and 20.8-24.5 mm pod size was found most suitable for each variety of green pea pods. Shelling efficiency of Arkel variety was found best at all the levels of moisture content and pod size. Shelling efficiency decreased with increase in moisture content and decrease in size of pods in all the varieties of pea under study.